The effect of higher out-of-pocket payments on drug prices and demand - Fabienne Loetscher; Christian Schmid; Michael Gerfin (University of Bern, Department of Economics, 2024)
Health care markets often lack a market force because the presence of health insurance undermines price signals. Patients have little incentive to shop for low-priced alternatives because they do not bear the full cost of their health care consumption. In turn, producers lack incentives to compete on prices. To improve efficiency in the pharmaceutical market, Switzerland introduced out-of-pocket price differentiation. As of July 1st 2011, substitutable pharmaceuticals with prices above a predefined threshold were subject to 20% coinsurance instead of the regular 10% coinsurance rate. Using comprehensive price data from public sources and patient drug use data from two Swiss health insurers, we analyze the price and demand response of this policy. Our analysis reveals an average pharmaceutical firm price reduction of 11%, with a more pronounced response from generic producers than from firms producing brand-name drugs. Regarding demand, we exploit a natural experiment in which one health insurer failed to timely implement the 20% coinsurance policy, resulting in quasi-random exposure to higher coinsurance. For patients affected by the policy, we find that the likelihood of purchasing a 20% coinsurance drug decreases by 4.3 and 1.3 percentage points for generic and brand-name drugs, respectively. These demand response estimates constitute lower bounds, as without the anticipatory behavior of producers, the demand response would likely have been more pronounced. Hence, our results indicate that the policy's effectiveness is based on the interaction between price-sensitive demand and profit-maximizing firms. Overall, our findings suggest that the (re)introduction of market-like mechanisms, such as price signals, can be effective in improving health care market efficiency.
Keywords: I11; I18; D12; D22; 330; Patient cost sharing; pharmaceutical pricing; patient demand; price signals; regulated competition; natural experiment